A Retrospective Review of Service Documentation by Physicians Following Families of Children Diagnosed with Autism Spectrum Disorder: Identifying Gaps in Communication. (1st June 2016) - Dunlap, H; Ler, S; Jegathesan, T; Minhas, R; Huber, J; Young, E
Abstract: BACKGROUND: Currently very little is reported on the best way for family physicians and pediatricians to manage children diagnosed with autism spectrum disorder (ASD). There is no standard way to monitor whether families manage to access services, how long they wait for services, and what they do if services are deferred/denied. Consequently, families are often left with limited guidance and support when accessing developmental services. OBJECTIVES: To evaluate the documentation patterns in medical charts of children diagnosed with ASD between 0-6-years old, whose care is shared between general and developmental pediatricians working in an inner-city setting. In particular, to study how physicians document the timeline and access to medical investigations and community services recommended by physicians. DESIGN/METHODS: A retrospective chart review of a random sample of approximately 40 patients diagnosed between 0-6-years old with ASD followed by general and developmental pediatricians is currently being conducted at St. Michael's Hospital. A systematic review of referral pathway to diagnosis, medical investigations, procurement of financial support and access to community services will be performed. Details obtained for review include date of recommendation, parent contact date, date on wait list, start date, and end date. RESULTS: Preliminary data from 30 patient medical records revealed inconsistencies in how services were documented by physicians. 80% of charts noted that Intensive Behavior Intervention (IBI), Applied Behaviour Analysis (ABA) and speech and language therapy (SLP) were recommended and/or accessed by families. However, the recorded timeline of access varied extensively, with start and end dates recorded in ≤ 20% of charts for ABA, ≤ 50% of charts for SLP and ≤ 70-80% of charts for IBI. ABA therapy appeared to be the most difficult to access, with uptake occurring in only 50% of recommendations. Medical investigation results were often present, however the dates for hearing and vision tests were inconsistently recorded by the pediatrician in the medical charts. Parent education and attendance to drop-in centres were not recommended or accessed in 50% and 25% of patient charts respectively. CONCLUSION: Preliminary results demonstrate inconsistent patterns of documentation by pediatricians following children with ASD when monitoring medical and community services, especially when recording timelines. Advocating for timely involvement in appropriate services requires an awareness of patients' past and current involvement in services. Thus, further research may be warranted to determine why certain services are less frequently documented, and how these gaps in communication can be improved to ensure optimal management.